(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The rapid progression in science and technology at an unmatched speed has opened door to e-commerce and m-commerce like never before. The retail markets are touching an impressive 600 million mark. Yet the surprising fact is that e-commerce constitutes barely 5% of the total share in contrast to the 15% in the US. This is clearly an indicative call for sufficient and timely action. What one needs is a SWOT analysis of the situation to study why we have failed to achieve the desired growth levels and how can the lacunae be filled. A deeper insight into the issue reveals that growing cyber crimes and frauds are the chief culprits. Even though the electronic medium is an easy way to buy and sell goods, most of the times, such transactions are wrought with fraudulent means thereby causing a sense of insecurity among buyers. Organizations and companies widely invest in employing the web services to launch new products. When such services are provided, they involve a lot of exchange of information which, if used for illegal purposes can cause serious security threats. The present paper attempts to review the techniques which help in detecting, preventing and predicting cyber crimes in the initial spaces. Ambitious initiatives like Digital India have no doubt increased the user base for internet and given the much needed push to the e-commerce and m-commerce trends; but we need to tread with caution. Inadequate cyber security has damaged the reputation of e-commerce sites and results in significant financial and information losses. The researcher attempts to study this growing nexus between online retailing and cyber theft.